2016
DOI: 10.3389/fped.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Brain Development in Sow-Reared and Artificially Reared Piglets

Abstract: IntroductionProvision of adequate nutrients is critical for proper growth and development of the neonate, yet the impact of breastfeeding versus formula feeding on neural maturation has to be fully determined. Using the piglet as a model for the human infant, our objective was to compare neurodevelopment of piglets that were either sow-reared (SR) or artificially reared (AR) in an artificial setting.MethodsOver a 25-day feeding study, piglets (1.5 ± 0.2 kg initial bodyweight) were either SR (n = 10) with ad li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(50 reference statements)
0
7
1
Order By: Relevance
“…Magnetic resonance spectroscopy (MRS) was used to non-invasively quantify metabolites both in the hippocampi and intervening tissue, as described previously. 13,14 In short, an MRS spin-echo chemical shift sequence was used to assess a voxel which centered over the left and right dorsal hippocampi with a size of 12 mm × 25 mm × 12 mm. Sequence parameters used for MRS data acquisition are as follows: TR = 3000 ms; TE = 30 ms; signal averages = 128 (water-suppressed scan) and 8 (non-water supressed scan); vector size = 1024 point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance spectroscopy (MRS) was used to non-invasively quantify metabolites both in the hippocampi and intervening tissue, as described previously. 13,14 In short, an MRS spin-echo chemical shift sequence was used to assess a voxel which centered over the left and right dorsal hippocampi with a size of 12 mm × 25 mm × 12 mm. Sequence parameters used for MRS data acquisition are as follows: TR = 3000 ms; TE = 30 ms; signal averages = 128 (water-suppressed scan) and 8 (non-water supressed scan); vector size = 1024 point.…”
Section: Methodsmentioning
confidence: 99%
“…Water-suppressed and non-water-suppressed data were acquired in institutional units, and all MRS data were analyzed using LC Model (version 6.3), using methods described previously. 13,14 Only neurometabolites for which a single data point was obtained for all piglets on the study were analyzed. Thus, neurometabolites in this analysis include: creatine + phosphocreatine (Cr+Pcr), glycerophosphocholine + phosphocholine (GPC+PCh), myo-inositol (mI), n-acetylaspartate (NAA), n-acetylaspartate + n-acetylaspartylglutamate (NAA+NAAG).…”
Section: Methodsmentioning
confidence: 99%
“…All pigs underwent magnetic resonance imaging (MRI) procedures at PND 32 or 33 at the Beckman Institute for Advanced Science and Technology Biomedical Imaging Center using Siemens MAGNETOM Trio 3T equipment with a Siemens 32-channel head coil. Methods described here are adapted from previous studies using MRI in pig (Radlowski et al, 2014;Jacob et al, 2016;Mudd et al, 2016b). Each pig underwent imaging protocols only once.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Studies have shown that volume of certain areas decreases in the presence of abnormal feeds, altered nutrition, and sensory deprivation in human (5156) and animal studies (57, 58). The difference in cerebellar size between feeding outcomes could be a similar issue, where the volume of the segmental brain regions is correlated with the activity.…”
Section: Discussionmentioning
confidence: 99%